2020
DOI: 10.1186/s12889-020-09039-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental modifiers of RTS,S/AS01 malaria vaccine efficacy in Lilongwe, Malawi

Abstract: Background: RTS,S/AS01 is the first vaccine against malaria to undergo pilot implementation, beginning in 2019 and vaccinating 360,000 children per year in Malawi, Ghana, and Kenya. The four-dose vaccine is given as a primary three-dose series with a fourth dose given approximately 18 months later. The efficacy of RTS,S/AS01 was variable among the 11 sites participating in the 2009-2014 phase III trial (MALARIA-055, NCT00866619), possibly due to differences in transmission intensity. However, a within-site exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Further research is needed to identify the ecological variables that might modify the impact of RTS,S through these mechanisms. In Lilongwe, Malawi, proximity to wetlands, identified using satellite imagery, was found to be related to RTS,S/AS01e efficacy, possibly because there was rebound malaria in higher transmission intensity areas [ 37 ]. The environmental context of households must be analyzed in conjunction with household ecological variables such as ITN and IRS use as well as household socioeconomic context.…”
Section: Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…Further research is needed to identify the ecological variables that might modify the impact of RTS,S through these mechanisms. In Lilongwe, Malawi, proximity to wetlands, identified using satellite imagery, was found to be related to RTS,S/AS01e efficacy, possibly because there was rebound malaria in higher transmission intensity areas [ 37 ]. The environmental context of households must be analyzed in conjunction with household ecological variables such as ITN and IRS use as well as household socioeconomic context.…”
Section: Ecologymentioning
confidence: 99%
“…The environmental context of households must be analyzed in conjunction with household ecological variables such as ITN and IRS use as well as household socioeconomic context. Each participant’s household roof type (metal versus grass), which is a socioeconomic indicator, was measured in the Malawi phase III trial site but was not found to be related to vaccine efficacy [ 37 ]. However, a recent analysis from Kintampo, Ghana, found that vaccine efficacy was higher in high-SES households, partially determined by household construction materials [ 48 ].…”
Section: Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…The MVIP in Ghana commenced in May 2019, shortly after the launch of the vaccine in Malawi in April 2019 (Bell et al, 2020;Hogan et al, 2020). Alongside Ghana and Malawi, Kenya is also one of the chosen countries in SSA for the MVIP (Hogan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…RTS,S, administered with AS01, is a liposome-based vaccine adjuvant containing monophosphorylate lipid A (MPLA) and is a recombinant antigen which was the first malaria vaccine to undergo pilot implementation, and currently vaccinates 360,000 children per year in Malawi, Ghana and Kenya [6,7]. However, clinical results have shown that the efficacy of RTS,S was ranging from 26% to 50% in infants and young children [8]. Therefore, research on malaria vaccines is continuing.…”
Section: Introductionmentioning
confidence: 99%